Gut Microbial Metabolite Short-Chain Fatt Acids Partially Reverse Surgery and Anesthesia-Induced Behavior Deficits in C57BL/6J Mice - Xu, Xiaohan; Wang, Kexin; Cao, Xuezhao; Li, Zhe; Zhou, Yongjian; Ren, Jiancong; Liu, Fang (Frontiers in Neuroscience, 2021)
Accumulating evidence has demonstrated that damages of gut microbiota are strongly associated with central nervous system (CNS) diseases such as perioperative neurocognitive disorders (PND). The present study investigated the role of gut microbial metabolites short-chain fatty acids (SCFAs) in surgery-induced cognitive deficits and neuroinflammation in hippocampus. Adult male C57BL/6J mice received either SCFAs mixture or saline orally for 4 weeks, and then partial hepatectomy was performed. The fecal supernatant of surgical mice was transplanted to normal mice for 3 weeks. Morris water maze (MWM) and Open-field test were used to evaluate behavioral performance on postoperative or post-transplantation days 3 and 7. In MWM test, pretreatment with exogenous SCFAs partially reversed surgery-induced impairments in crossing times and the time spent in target quadrant on postoperative day 3 (p < 0.05, p < 0.05, respectively). In open-field test, compared with the surgical mice, exogenous SCFAs administration prior to surgery partially improved the locomotor activity (p < 0.05) and anxiety-like behavior (p < 0.05) on postoperative day 3. Surgical trauma and anesthesia enhanced ionized calcium-binding adapter molecule 1 (Iba-1) expression (p < 0.001), increased levels of interleukin (IL)-1β (p < 0.001) and IL-6 (p < 0.001) and inhibited SCFAs production (p < 0.001) on postoperative day 3. The expression of brain-derived neurotrophic factor (BDNF) was also decreased (p < 0.001). Overall, surgical trauma and anesthesia exacerbated cognitive impairment, enhanced neuroinflammatory responses and inhibited SCFAs production. Pretreatment with SCFAs attenuated these effects partially by reversing microglial overactivation, inhibiting neuroinflammatory responses and enhancing BDNF expression.